The Influence of Promoter Reputation, Ticketing System, Price, and Celebrity on Repurchase Intention of Concert Tickets by Mecimapro - Salsabila, Dinda Diana; Yusrin, Nur Amalyna (Sean Institute, 2025)
This study aims to analyze the influence of Promoter Reputation, Ticketing System, Price, and Celebrity on Repurchase Intention for concert tickets organized by Mecimapro. A quantitative approach was used, distributing questionnaires to 110 respondents who had purchased tickets from Mecimapro. Data analysis was conducted using the SEM-PLS method. The findings reveal that promoter reputation (T-Statistic = 4.428, P-Value = 0.000) and price (T-Statistic = 5.741, P-Value = 0.000) significantly influence repurchase intention. In contrast, the ticketing system (T-Statistic = 0.644, P-Value = 0.521) and celebrity (T-Statistic = 1.845, P-Value = 0.068) do not have a significant impact. This study underscores the importance of promoter reputation and ticket pricing as primary factors in building customer loyalty. Promoters are advised to focus on improving service quality and adopting competitive pricing strategies to enhance repurchase intention